Protective efficacy of an H5/H7 trivalent inactivated vaccine (H5-Re13, H5-Re14, and H7-Re4 strains) in chickens, ducks, and geese against newly detected H5N1, H5N6, H5N8, and H7N9 viruses - Xian-ying ZENG; Xin-wen HE; Fei MENG; Qi MA; Yan WANG; Hong-mei BAO; Yan-jing LIU; Guo-hua DENG; Jian-zhong SHI; Yan-bing LI; Guo-bin TIAN; Hua-lan CHEN (Journal of Integrative Agriculture, 2022)
Some H5 viruses isolated in poultry or wild birds between 2020 and 2021 were found to be antigenically different from the vaccine strains (H5-Re11 and H5-Re12) used in China. In this study, we generated three new recombinant vaccine seed viruses by using reverse genetics and used them for vaccine production. The vaccine strain H5-Re13 contains the hemagglutinin (HA) and neuraminidase (NA) genes of an H5N6 virus that bears the clade 2.3.4.4h HA gene, H5-Re14 contains the HA and NA genes of an H5N8 virus that bears the clade 2.3.4.4b HA gene, and H7-Re4 contains the HA and NA genes of H7N9 virus detected in 2021. We evaluated the protective efficacy of the novel H5/H7 trivalent inactivated vaccine in chickens, ducks, and geese. The inactivated vaccine was immunogenic and induced substantial antibody responses in the birds tested. Three weeks after vaccination, chickens were challenged with five different viruses detected in 2020 and 2021: three viruses (an H5N1 virus, an H5N6 virus, and an H5N8 virus) bearing the clade 2.3.4.4b HA gene, an H5N6 virus bearing the clade 2.3.4.4h HA gene, and an H7N9 virus. All of the control birds shed high titers of virus and died within 4 days post-challenge, whereas the vaccinated chickens were completely protected from these viruses. Similar protective efficacy against H5 viruses bearing the clade 2.3.4.4h or 2.3.4.4b HA gene was observed in ducks and geese. Our study indicates that the newly updated H5/H7 vaccine can provide solid protection against the H5 and H7N9 viruses that are currently circulating in nature.